THE EFFECT OF COOPERATIVE LEARNING MODEL USING PHET SIMULATION ON PHYSICS STUDENT’S ACHIEVEMENT - nabila aulia rahma; Ratnawulan Ratnawulan; Letmi Dwiridal; Renol Afrizon (PILLAR OF PHYSICS EDUCATION, 2023)
The purpose of this study was to measure students' academic skills using a group survey model using Phet.. These skills can be acquired by adopting an appropriate learning model in terms of mastery of materials and skills.. A survey was conducted at Senior High School and information was obtained that students' learning results still needed to be higher. Students' learning outcomes can be improved by using learning models and media. The solution that can be done is to apply the GO type cooperative model using PhET simulation. This research is pseudo-experimental, posttest-only design. The population of this study were all XI science classes of Senior high scholl , registered in the 2022/2023 academic year. Sampling was done using a purposive sampling technique, grade XI IPA 1 and grade XI IPA 2  classes were selected as samples. The instruments used were posttest questions for knowledge-skills observables for attitudes and skills-skills, and the research hypothesis was tested using the t-test. Research results using t-test lead to the conclusion that in students' knowledge competency, the value of Tcounts 5,279> Ttable 1,994437. Regarding attitude competency, the value of T is 11,89> Ttable 1,994437. In the skill competency, the value of Tcount is 3,3580> Ttable 1,994437. This shows that the hypothesis is accepted. So, motivating in the form of a posttest can improve the learning outcomes of physics students in Class XI IPA at Senior high school in the 2022/2023 school year.